Field and simulation study of the rational retracement channel position and control strategy in close‐distance coal seams. Issue 7 (31st March 2022) - Lv, Kai; He, Fulian; Li, Liang; Xu, Xuhui; Qin, Binbin
Abstract: Different from single coal seam mining, the stress evolution in the end mining stage of close‐distance coal seams is extremely complex. The unreasonable position and support of the lower retracement channel will cause serious deformation and damage to the surrounding rock. Taking the Yanzishan coal mine as the engineering background, the deformation and failure characteristics of the retracement channel under different overlay environments and the key influencing factors of position design were discussed by numerical simulation, theoretical analysis, and field investigation. The results show that the coupling superposition of upper coal pillar high stress and mining dynamic pressure will form a dangerous area with severe ground pressure behavior. The retracement channel should be preferentially designed in zone A (overlying mining roadways), followed by zone B (overlying end‐mining coal pillar), and finally, zone C (overlying section coal pillar). In addition, the rational horizontal distance between the lower retracement channel and the upper end‐mining coal pillar should make the channel in a good stress environment. The safety distance between the retracement channel and the nearest main roadway (end‐mining coal pillar width) should be greater than the severe range of advance abutment pressure. Finally, the design principle and control strategy for the lower retracement channel is proposed. The feasibility and rationality of the study are verified by industrial applications. Abstract : Considering Yanzishan coal mine as the engineering background, the position of the lower retracement channel can be divided into three: zone A, zone B, and zone C, which, in turn, are located below mining roadways, end‐mining coal pillar, and section coal pillar, respectively. Numerical simulation, theoretical analysis, and field investigation were used to discuss the deformation and failure characteristics of the retracement channel, the load transfer law of residual coal pillar, and the range of advanced abutment pressure. Finally, the design principle and control strategy for the lower retracement channel is proposed, and the field tests were carried out in the N0381 working face.